2015
DOI: 10.18632/oncotarget.4365
|View full text |Cite
|
Sign up to set email alerts
|

Activation of microRNA-494-targeting Bmi1 and ADAM10 by silibinin ablates cancer stemness and predicts favourable prognostic value in head and neck squamous cell carcinomas

Abstract: Tumor initiating cells (TICs) possessing cancer stemness were shown to be enriched after therapy, resulting in the relapse and metastasis of head and neck squamous cell carcinomas (HNC). An effective therapeutic approach suppressing the HNC-TICs would be a potential method to improve the treatments for HNC. We observed that the treatment of silibinin (SB) dose dependently down-regulated the ALDH1 activity, CD133 positivity, stemness signatures expression, self-renewal property, and chemoresistance in ALDH1+CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 56 publications
0
59
0
Order By: Relevance
“…Red (> 650 nm) fluorescence emission from 10,000 cells illuminated with blue (488 nm) excitation light was measured with a FACSCalibur (Becton Dickinson, Mountain View, CA, USA) using CellQuest software. 21 …”
Section: Cd44 Staining By Flow Cytometry Analysismentioning
confidence: 99%
“…Red (> 650 nm) fluorescence emission from 10,000 cells illuminated with blue (488 nm) excitation light was measured with a FACSCalibur (Becton Dickinson, Mountain View, CA, USA) using CellQuest software. 21 …”
Section: Cd44 Staining By Flow Cytometry Analysismentioning
confidence: 99%
“…Mounting evidences have demonstrated that the dys-regulation of stemness marker expression contributes to the pathogenesis of diseases, especially its roles in tumorigenesis2021. Some aberrant stemness marker expressions such as Bmi1, CD133, or Sox2 have been found to be involved in the progression of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…qRT–PCRs of mRNAs are reverse-transcribed using the Superscript III first-strand synthesis system for RT–PCR (Invitrogen Life Technologies, Carlsbad, CA, USA). qRT-PCR reactions on resulting cDNAs were performed on an ABI StepOne™ Real-Time PCR Systems (Applied Biosystems)20. The primer sequences listed below:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations